Miseries among the People of Bhojpur - A Village of Raisen District Madhya Pradesh India: Exploring the challenges and potential solutions for the people of Bhojpur village in Raisen District, Madhya Pradesh, India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper discusses the miseries facing by the people of Bhojpur village district Raisen Madhya Pradesh India. It also reveals us about the cultural and social life of people and the problems which they are facing. A large segment of village still suffers deprivation and discriminatory attitudes by the Government agencies. It is necessary to mobilize the village development, if the country has to top progress in all sphere of development. The paper finally illustrates the present situation of the village and the deprivation of government facilities and the sick position of village development. The paper also contains few suggestions which, if implemented on ground level can eradicate the miseries of village and can also uplift the income related problems.